The features of summary background electric activity of the hypothalamus of rats under conditions of chronic caffeine alimentation - T. G. Turitskaya; S. N. Lukashev; V. P. Lyashenko; G. G. Sidorenko (Regulatory Mechanisms in Biosystems, 2018)
One of the factors of the environment which essentially shifts homeostasis is diets which contain caffeine. The aim of the study was to find out the basic characteristics of background electrical activity of trophotrophic and ergotrophic zones of the hypothalamus in conditions of chronic caffeine alimentation. Experiments were carried out on non-linear white male rats. The first group consisted of control animals (n = 22). The second group (n = 24) was represented by the animals that were given pure caffeine in an amount of 150 mg/kg/day with their meal. The registration on a electrohypothalamogram was carried out in conditions of acute experiment, every 2 weeks for 12 weeks. The spectral (mkV2) and the normalized power (%) of electrohypothalamogram waves were analyzed within the common frequency band. The analysis of the results allowed us to establish a certain specificity of the reaction of the neuronal system of the trophotropic and ergotropic zones of the rat hypothalamus to the effect of chronic caffeine alimentation. The main difference in the reactive state of electrophysiological indices in the trophotrophic zone of rats is the lack of a typical desynchronization from the 4th to the 8th week of the study and the hypersynchronization after 12 weeks of the experiment. The most probable mechanism that explains the results obtained is the ultra-powerful GABA-ergic modulation of this zone, the main energy-accumulating center. Perhaps, this powerful inhibitory resource in this cerebral locus is the main stress-limiting factor that makes this zone of the central nervous system of rats less sensitive to caffeine exposure. Instead, under the influence of chronic caffeine load in the ergotropic zone of the hypothalamus, after 6 weeks of the experiment desynchronous high-frequency rhythms dominated. During the subsequent time of the experiment, we observed a decrease in both low-frequency and high-frequency components of the electrohypothalamogram of this zone. This gives reason to assume that the key component of the neurophysiological response of the posterior hypothalamus of rats to the caffeine ration is the powerful glutamatergic effects on the pre-synaptic and post-synaptic neurons under conditions of reactive exhaustion of local neurosynthetics. Caffeine depletion of the hypothalamic neurotransmission at the end of the experiment is replaced by an effective adaptive ergotropic restoration of neurosynthetic activity in this locus of the central nervous system of rats. Thus, caffeine has a powerful activating effect on the ergotropic function of the posterior hypothalamus of rats. Such a difference in the chronic effect of caffeine on the trophotropic and ergotropic zone of the rat hypothalamus is primarily due to the different mediator support of these zones underlying their physiological purpose. GABA is the main mediator of the trophotropic zone and the main neurotransmitter of its synchronous activity. At the same time, neurotransmitter support of the ergotropic zone is represented by glutamate, which, along with other agents, implements its desynchronous activity. Since caffeine stimulates excitation, activating the pathways traditionally associated with motivational and motor reactions in the brain, it can be assumed that this explains the fact of a more powerful influence of caffeine precisely on the ergotrophic zone of the hypothalamus.